Understanding the role of push and pull factors on agricultural land expansion: A case study of Adaba and Adiyo district, Ethiopia - Teweldebrihan, Meseret Dawit; Gebehiwot, Tagel; Teklewold, Hailemariam; Olumana Dinka, Megersa; Abera, Wuletawu; Tamene, Lulseged D. (Elsevier, 2023)
Understanding the human-forest relationship is key to sustainable development and forest management. The increase of agricultural land expansion mainly focuses on satisfying the competing interest amongst stakeholders and rural households, which neglects the impact of forest losses. The study looked at rural households' farmland expansion dynamics in Adaba (Oromia Region) and Adiyo, located in the Southern Nations, Nationalities, and People's Region (SNNR) of Ethiopia. Thus, the study identified the role of push and pull factors in rural households’ agricultural land expansion using primary and secondary data. We found that the livelihood of the rural households significantly impacts farming land expansion at the expense of forest resources (deforestation). In addition, we noticed that the increase in household size and living expenses, followed by the need for income diversification, are amongst the major drivers directly causing farmland expansion. In contrast, economic pressure was generally found to be the key push factor for most rural households to expand their farming land. Hence, some farmers were “pulled” by the current economic return and market attraction of timber due to the booming market demand, which was seen as one of the reasons for forest loss. These findings also reported the negative impacts of agricultural expansion on biodiversity and the environment, which need alternative agricultural development pathways.